Effect of different crop establishment methods on yield attributes, yield and economics of basmati rice (Oryza sativa) cultivars - YADAV, VIVEK; MISHRA, D N; SINGH, RAJENDRA; KUMAR, VIKAS (The Indian Journal of Agricultural Sciences, 2026)
A field experiment was conducted during two consecutive kharif season of 2009 and 2010 at Zonal Research Station, Nagina, Bijnor to find out performance of 4 basmati rice (Oryza sativa L.) varieties (Taraori basmati, Pusa Basmati 1, Pusa Sugandha 4 and Pusa Sugandha 5) under 3 establishment methods (direct seeding, drum seeding and transplanting). Highest values of yield attributes and yield was recorded under transplanting ( 40.18 q/ha) and in varieties with Pusa Sugandha 5 (42.74 q/ha). Highest cost of cultivation was recorded under transplanting with Pusa Sugandha 5 (Rupees 30 594.00) however drum seeding with Pusa Sugandha 5 was prove to be most remunerative combination (Rupees 49 119.05). Highest values of B:C ratio (1.97) was also recorded under combination of drum seeding with variety Pusa Sugandha 5.